What are we protecting? Rethinking relational values and nature(s) - Sam Campbell; Laura Gurney (Ecosystems and People)
Relational values have been proposed as a way of capturing more inclusively the relationships that people have with nature and have been adopted within the conceptual framework of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). Relational values literature has taken strides towards a more comprehensive appreciation of human-nature interactions than previous frameworks. However, we see an opportunity to build further on the relational values concept through the frame of political ontology. In this Perspective, we argue that, in order to understand people’s relationships with their environments, we must first ask the following question: what is nature to those who value their relationships with it? Comprehending the multiple natures that people experience and value can help us to achieve equitable and representative conservation policy, explain actions and behaviours, and identify obstacles to engagement with conservation agendas.